The efficiency of ministries in transposing EU directives: Evidence from Ireland. (April 2018) - Thomas, Martha
Studies on how the European Union's (EU) directives are transposed by national governments have consistently concluded that bureaucratic efficiency of member-states is a crucial determinant of timely transposition. These studies usually focus on the bureaucracy as a whole and utilize static aggregate measures of efficiency. They do not examine how differences in management performance among ministries impact transposition outcomes. This study advances our insight by disaggregating the features of the bureaucracy and examining whether differences in ministries' decentralization, leadership, past experience with timely transposition, and budgetary allocations explain how bureaucratic processes impacts effective transposition. An original dataset focusing on transposition of EU directives by Ireland is constructed and applied to the problem. Quantitative analysis, informed by original field research, reveals that significant differences in performance can exist among a member state's ministries. Ministerial leadership, past experience, and favorable budgetary allocations predict the most timely transposition of Brussels' directives.